155k views
0 votes
What is a rule for

h


(
x
)

h

(x) space, h, prime, left parenthesis, x, right parenthesis, space if

h
(
x
)
=

1
x

h(x)=
sin
−1
x

User Pushkr
by
5.8k points

1 Answer

3 votes

Answer:

Step-by-step explanation:f(h(x))= 2x -21

f(x)= x^3 - 6

h(x)=\sqrt[3]{2x-15}

WE need to find f(h(x)), use composition of functions

Plug in h(x)

f(h(x))=f(\sqrt[3]{2x-15})

Now we plug in f(x) in f(x)

f(h(x))=f(\sqrt[3]{2x-15})=(\sqrt[3]{2x-15})^3 - 6

cube and cube root will get cancelled

f(h(x))= 2x-15 -6= 2 x-21

User Alex Dovzhanyn
by
6.3k points